Outcomes after surgery and postoperative radiotherapy for perineural spread of head and neck cutaneous squamous cell carcinoma. Issue 6 (6th May 2015) - Warren, Timothy A.; Panizza, Benedict; Porceddu, Sandro V.; Gandhi, Mitesh; Patel, Parag; Wood, Martin; Nagle, Christina M.; Redmond, Michael
Abstract: Background: Queensland, Australia, has the highest rates of cutaneous squamous cell carcinoma (SCC). Perineural invasion (PNI) is associated with reduced local control and survival. Methods: A retrospective review of a prospective database of patients with clinical PNI from cutaneous SCC of the head and neck (SCCHN) treated with surgery and postoperative radiotherapy (PORT) between 2000 and 2011 and a minimum of 24 months follow‐up. Patients were excluded if immunosuppressed, had non‐SCC histology, or were treated palliatively. Results: Fifty patients (mean age, 60 years) with median follow‐up of 50 months were included in this study. A total of 54.8% of known primary tumors had incidental PNI. Ten percent had nodal disease at presentation. MRI neurogram was positive in 95.8%. Recurrence‐free survival (RFS) at 5‐years was 62%. Five‐year disease‐specific survival (DSS) and overall survival (OS) were 75% and 64%, respectively. There were no perioperative deaths. Conclusion: This report demonstrates that long‐term survival is achievable in patients with clinical PNI from cutaneous SCCHN after surgery and PORT. © 2015 Wiley Periodicals, Inc. Head Neck 38: 824–831, 2016